A large-eddy-simulation-based numerical wave tank for three-dimensional wave-structure interaction. (15th December 2021) - Christou, Aristos; Stoesser, Thorsten; Xie, Zhihua
Abstract: A three-dimensional numerical wave tank (NWT) based on the open-source large eddy simulation (LES) code Hydro3D is introduced. The code employs the level set and immersed boundary methods to enable accurate computations of the deformation of the water surface and to account for solid structures in the fluid domain, respectively. The spatially-filtered Navier–Stokes (N–S) equations are solved on a staggered Cartesian grid using the finite difference method while time advancement is achieved using the fractional-step method based with a three-step Runge–Kutta scheme. Velocities and pressure are coupled with the Poisson equation and its solution is obtained via a multi-grid technique. The code is then applied to predict the progression and damping of monochromatic waves and the interaction of non-linear waves with various submerged obstacles. The accuracy of Hydro3D is confirmed by comparing numerical results with data of previously reported laboratory experiments. Comparisons of numerically predicted and measured water-levels, local velocity and pressure fields and forces acting on structures under the influence of incoming waves with laboratory data are convincing and confirm that the code is able to predict accurately three-dimensional wave-structure interaction. Highlights: A large-eddy simulation based numerical wave tank has been refined. The method is validated for complex wave-structure interaction. Good agreement is achieved. The method is applicable to three-dimensional WSI problems.